Wyjście z laboratorium - Momro, Jakub (Przestrzenie Teorii, 2019)
The article is a critical insight into Ryszard Nycz’s theoretical and antropological project included in his book, Culture as a Verb. Sounding out New Humanities. The fundamental argument is based on the archeology of Nyczean concepts, and their philosophical and socio-political implications. The analytical process focuses on three points. Firstly, the issue is the non-reducing meaning of the cultural experiment, which is the foundation of the “new” epistemology. Secondly, the question is the new idea of temporality, historicity, and relations between nature and culture. Thirdly, the focus is on the concept of praxis.